Model Analysis of Increasing Lecturer Job Satisfaction and Its Impact on Organizational Citizenship Behavior in the Era of Society 5.0 - Darwin Lie; Elly Romy; Gloria Miagina Palako Djurubassa; Acai Sudirman (Journal of Innovation in Educational and Cultural Research, 2024)
In the Society 5.0 era which is marked by digital transformation and paradigm changes in education, research on models for increasing lecturer job satisfaction is becoming increasingly important. During this transformation, lecturer job satisfaction not only impacts individual performance but also has the potential to influence organizational citizenship behavior and overall teacher performance. This study aims to analyze the antecedents and consequences of lecturer job satisfaction and their impact on organizational citizenship behavior. This study used a quantitative approach with PLS-SEM analysis. This study used a sampling technique, namely probability sampling with proportional cluster stratified random sampling so that the acquisition of samples amounted to 120 lecturers. The results of the data analysis confirm that work discipline and motivation have no significant effect on lecturer job satisfaction. Compensation has a significant effect on lecturer job satisfaction. Lecturer job satisfaction has a significant effect on organizational citizenship behavior. Lecturer job satisfaction has a significant effect on teacher performance. This study concludes that the process of fostering and developing lecturers is an activity the university must carry out to adapt to changes and developments. Universities must evaluate the level of lecturer job satisfaction and lecturer performance to encourage more competitive tertiary performance. The implication of this study states that lecturers who are satisfied with their work tend to have high motivation and are committed to providing quality teaching. Lecturers who are satisfied with their jobs tend to be more likely to engage in OCB.